RESILIENSI MAHASISWA BIMBINGAN DAN KONSELING UNIVERSITAS AHMAD DAHLAN DITINJAU DARI PERBEDAAN JENIS KELAMIN - Wahyudi, Amien (JURNAL KONSELING GUSJIGANG, 2020)
The purpose of this study was to see differences in the resilience of student guidance and counseling based on sex. The data collection tool in this study is a resilience scale that has been tested for validity and reliability. The number of research subjects was 68 students consisting of 34 male students and 34 female students. The results of the study through independent calculation of the sample t test showed that there were no traditional differences between male and female students.